Mapping the Effects of Potassium on Fuel Conversion in Industrial-Scale Fluidized Bed Gasifiers and Combustors - Teresa Berdugo Vilches (MDPI AG, 2021)
Potassium (K) is a notorious villain among the ash components found in the biomass, being the cause of bed agglomeration and contributing to fouling and corrosion. At the same time, K is known to have catalytic properties towards fuel conversion in combustion and gasification environments. Olivine (MgFe silicate) used as gasifier bed material has a higher propensity to form catalytically active K species than traditional silica sand beds, which tend to react with K to form stable and inactive silicates. In a dual fluidized bed (DFB) gasifier, many of those catalytic effects are expected to be relevant, given that the bed material becomes naturally enriched with ash elements from the fuel. However, a comprehensive overview of how enrichment of the bed with alkali affects fuel conversion in both parts of the DFB system is lacking. In this work, the effects of ash-enriched olivine on fuel conversion in the gasification and combustion parts of the process are mapped. The work is based on a dedicated experimental campaign in a Chalmers DFB gasifier, wherein enrichment of the bed material with K is promoted by the addition of a reaction partner, i.e., sulfur, which ensures K retention in the bed in forms other than inactive silicates. The choice of sulfur is based on its affinity for K under combustion conditions. The addition of sulfur proved to be an efficient strategy for capturing catalytic K in olivine particles. In the gasification part, K-loaded olivine enhanced the char gasification rate, decreased the tar concentration, and promoted the WGS equilibrium. In the combustion part, K prevented full oxidation of CO, which could be mitigated by the addition of sulfur to the cyclone outlet.